Influence of the Sedimentation Conditions on the Formation of Reservoir Rocks of the Bobrikovsko-Radaevskian Deposits - S.E. Valeeva; A.G. Baranova; B.V. Uspensky (Учёные записки Казанского университета: Серия Естественные науки)
It is important to study the core materials from wells not only to determine the reservoir properties of rocks and fluids containing them, but also to recover the history of accumulation of the studied sediments. Thus, one of the most popular methods of recovery of the paleogeographic conditions of sedimentation is based on the particle size distribution coefficients, as well as charts and graphs resulting from their interpretation. This paper presents the data from studying the particle size distribution by determining the particle size distribution coefficients and their interpretation, also with the help of the Passega diagrams. Using this methodology, a genetic interpretation of sandy sediments, which form the Bobrikovskian reservoir layers, is obtained. The conditions of their sedimentation are revealed.